PENGARUH PERBAIKAN GIZI KESEHATAN TERHADAP PRODUKTIVITAS KERJA - ARI AGUNG, I GUSTI AYU (PIRAMIDA, 2012)
The prevalance of iron deficiency is still high in Indonesia. Iron is an essentialcomponent of haemoglobin (essential of cell respiration/carrier of O2 and CO2),component several enzymes that play an important role in some metabolic processes.Iron deficiency causes a reduction in amount of enzymes, among others the enzymesakonitase, katalase, monoaminoksidase, mieloperoksidase, ribonukleotidil reduktase,suksinat dehirogenase, tirosin hidrolse, triptofan pirrolase dan xantin oksidase.Overcoming deficiencies in nutrition and controlling prevailing diseases producesstronger, more energetic workers, reduces to number of work days lost because of illness,lengthens the working life span and increases cognitive skills. The flow of earning isthereby increased above what it would have been in the abcence of improved nutritionand health.Many studies indicate measurable correlation between better nutrition, healthand higher productivity and better income, which have important functionalconsequences of public health, social and economic significance.
Keywords: nutrition, health, iron deficiency, productivity